2017
DOI: 10.1111/ene.13335
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of aseptic central nervous system infections in southern Germany – demographic, clinical and laboratory findings

Abstract: Polymerase chain reaction tests for HSV, VZV and EV in CSF and TBE serology determined the causative virus in over 60% of tested patients. The age of affected patients, seasonal distribution, disease course and inflammatory changes in CSF differ between groups of patients affected by the most common viral infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
1
12
2
Order By: Relevance
“…In line with previous studies, meningitis was the main clinical manifestation of enteroviral nervous system infection (Han et al, 2016;Kaminski et al, 2017). Notably, 22% of the study patients with meningitis reported a sudden onset of headache that led to the initial suspected diagnosis of subarachnoidal haemorrhage.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In line with previous studies, meningitis was the main clinical manifestation of enteroviral nervous system infection (Han et al, 2016;Kaminski et al, 2017). Notably, 22% of the study patients with meningitis reported a sudden onset of headache that led to the initial suspected diagnosis of subarachnoidal haemorrhage.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, another five patients who presented clinically with meningitis also showed cranial nerve involvement. While cranial nerve involvement is common in children (Messacar et al, 2015), it has not been reported in clinical studies of adults with enteroviral CNS infection (Hong et al, 2014;Kaminski et al, 2017). However, sporadic cases of vestibulocochlear nerve disturbance in the context of enteroviral CNS infection have been described (Schattner et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment modalities are limited, with the exception of the immune‐mediated diseases and those with a defined biochemical cause that lends itself to specific therapy such as Pompe disease . Immune‐mediated diseases of the central nervous system are a heterogenous group of disorders characterized by specific antibodies to central nervous system proteins such as the autoimmune encephalitides and neuromyelitis optica. Significant progress has been made in the diagnosis and treatment of these .…”
mentioning
confidence: 99%